Study of Bellandur Lake Series and Mitigation of Further Damage - Verma, Rinku; Venkatesh, D. A.; Perodi, Yusuf (Advances in Social Sciences Research Journal, 2022)
Bellandur and Varthur lakes are two large lakes located in the East of Bangalore urban district. Varthur lake in Bangalore receives water from 9 lakes; together with Varthur Lake they form the Varthur Lake Series. Bellandur lake is one of these 9 lakes and is one of the largest lakes in Bangalore. Bellandur Lake in turn receives water from 29+ lakes. During October-November 2017, 45 lake subseries of Varthur lake and Bellandur lake were visited, studied and recommendations were submitted to Karnataka Lake Conservation & Development Authority (KLCDA). The same is presented in this paper. In this study, the subseries of Varthur and Bellandur lakes are referred to as Varthur Bellandur Lake Series.